Zeitliche Beschränkung bei Behinderten-Parkplatz. - (:unkn) unknown (Beck, 2002)
VGH Baden-Württemberg, Beschluss vom 22.8.2001 - 5 S 69/01. difu
Keywords: Individualverkehr; Stellplatz; Parkplatz; Parken; Behinderter; Behindertenparkplatz; Beschränkung; Zeitbeschränkung